¿Qué hacer con los pobres? Elites y sectores populares en Santiago de Chile 1840-1895 - A. Romero, Luis (Ariadna Ediciones, 2007)
Study on the phenomenon of the poor and poverty in Santiago city in the 19th century, and the reaction of the political and economic elite